Koherensi Wacana Sesorah Perkawinan Dalam Bahasa Jawa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT This research is aimed to describe the discourse of Javanese wedding speech. The description deals with lingual markers that support the coherence, kinds of relation in the inter parts of the coherence, and the patterns of the coherence. This research is expected to give a theoretical benefit in discourse analysis and a practical benefit especially in arranging the Javanese wedding speech. The data in the form of Javanese wedding speech are obtained both spoken and written resourses. The spoken data obtained from the trancription of the Javanese speech at the wedding ceremony in Yogyakarta, while the written data are obtained from book with consist of Javanese wedding speech. The results are then classified, reduced, and analyzed by employing the "padan-referensial" and " agih" methods followed by mutation, substitution, deletion, and paraphrasing techniques. The methods and techniques are applied to carry out the discourse analysis. Based on the analysis, it shows that in the discourse of Javanese wedding speech there are eight relations. They are: (1) explanation relation (the lingual markers which indicate the relation are ateges 'meaning', inggih menika `namely')